The Effect of Drying Temperature and Time on The Chemical Characteristic, Total Phenolic Content, and Organoleptic Properties of Black Garlic Herbal Tea - Kiptiyah, Sakina Yeti; Widyananda, Bina Indah; Khairiah, Khairiah (Indonesian Journal of Food Technology, 2024)
Black garlic is a functional food known to be beneficial for health. Most people favor the organoleptic properties produced, so it needs handling to improve, namely by drying, which produces black garlic herbal tea products. This study aims to determine the effect of drying temperature and time on chemical characteristics, total phenolic content, and the organoleptic properties of black garlic herbal tea. The experiment was conducted with a two-factor, completely randomized design. The first factor is drying temperature, which consists of two levels (50 and 60⁰C). The second factor is drying time, which consists of two levels (5 and 6 hours). The observation results were analyzed using analysis of variance (ANOVA) and continued with DMRT further test at a 5 % confidence level. The results showed that black garlic herbal tea's temperature and drying time significantly affected chemical characteristics, total phenolic content, and color but had no significant effect on aroma, taste, and overall. The chemical characteristic results in the 60 ⁰C drying temperature for 6 hours contained 7.65 % moisture content, 2.98 % ash, and 4.06 mgGAE/g total phenolic content.